ICAN week 3.0 @ FBM - UiTM, Faculty of Business and Management (UiTM, 2024)
Faculty or Management and Business: has successfully organized 'ICAN Week 3.0, an annual event that brought together students, tile community, and the industrial sector through various beneficial programs. With the participation of over 40 companies and organizations, the event offered more than 30 industry-sharing sessions, interactive workshops, and activities focused on human capital development. ICAN Week began with the opening ceremony by the Director of the Industry Networking Centre (INC), Professor Dr. Muhammad Hussain Ismail, who emphasized the importance of strong ties between industry and academia.